The simulation modeling of a container port’s operations; verification and validation - Ng, Zhong Jin (2015)
A simulation model of a container terminal was created to study the utilization of container storage areas and lorries that transport the containers to their destination, the objective being to optimize container space allocation and to improve efficiency of port operations. A manual simulation model was first developed and a trial run involving multiple replications of the container terminal operations was conducted. The model was then recreated as a computer simulation model in FlexSim (a 3D simulation software). The same number of replications of the computer simulation model was performed for an 18-day operation. Both models were validated by comparing the results. Simulation replications were made and the output data was analyzed. The simulation revealed that the Container Yard and Transit Yard should be sized to accommodate an average of 331 and 165 containers respectively; the Lorry Park for 134 lorries on average. The average overall cycle time for clearing containers was 151.9 hours; of these, some 44% of the time was attributed to wait times at the Container Yard and 25% was spent transporting the containers to their destinations. For 51.8% of the time, there were sufficient Red lorries servicing the Red shipping line, while Blue lorries were adequate 70.8% of the time.